Student-centered Learning and Extensive Reading - Renandya, Willy A. (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
The aim of my talk is to explore the relationship between student-centred learning (SCL) and extensive reading (ER), and how to bring the two closer together in the classroom. I will first (re)examine the concepts behind SCL and the key features normally associated with this approach to learning, i.e., the degree of personalized learning, level of student engagement and motivation, and student control over learning. I will then discuss the theoretical underpinnings (e.g., input theory and skill learning theory) and key characteristics (e.g., appropriate reading materials in terms of choice and variety) of ER in order to determine the extent to which ER is compatible with SCL. I will then provide research evidence demonstrating how the marriage between SCL and ER could lead to enhanced student learning, i.e., greater mastery of the target language and a more positive attitude towards language learning.